(untitled) (Journal of Finance, Business and Management Studies, 2021)
A new virus and the illness caused by it, first appeared in China at the end of 2019, then quickly spread to the rest of the World and became a pandemic. This pandemic has caused a global crisis in many ways including socially, financially, economically but most importantly a health crisis. This pandemic has not only rattled countries’ economies but has also impacted financial markets. Whether this impact is positive or negative, the degree of the impact, which countries has been more and less affected, impact with regards to industry segment, whether there’s a difference between the impact on developed nations and developing nations requires further research. With that in mind, selected countries’ stock markets have been analyzed and interpreted during the pandemic in this research paper using charts created with datas of COVID-19 and stock market indices. According to the findings it can be stated that with the increase in the number of COVID-19 cases and deaths there have been tremendous drops in the stock markets. It has been observed that indices during COVID-19 show a similar trend with the epidemic in some countries.